High-throughput structures of protein–ligand complexes at room temperature using serial femtosecond crystallography. (2019) - Moreno-Chicano, Tadeo; Ebrahim, Ali; Axford, Danny; Appleby, Martin V.; Beale, John H.; Chaplin, Amanda K.
No abstract available